Endogenous Information Acquisition in Coordination Games. - Myatt, D; Wallace, C (Department of Economics (University of Oxford), 2009)
In the context of a “beauty contest” coordination game (in which pay-offs depend on the proximity of actions to an unobserved state variable and to the average action) players choose how much costly attention to pay to various informative signals; they endogenously select information sources and how carefully to listen to them. Each signal has an underlying accuracy (how precisely it identifies the state variable) and a clarity (how easy it is for players to understand what the signal says). The unique information-acquisition equilibrium has interesting properties: only a subset of signals are assigned positive weight and attention; these are the clearest signals available, even if such signals have poor underlying accuracy; the size of the subset shrinks as the complementarity of players’ actions becomes more acute; and, if actions are more complementary, the information endogenously acquired in equilibrium is more public in nature.